2000
DOI: 10.1007/s001980070082
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Subsequent Bone Density Response to Intermittent Cyclical Therapy with Etidronate from Initial Density Response in Patients with Osteoporosis

Abstract: We investigated whether an increase in lumbar spine bone mineral density (LS BMD) at 6 months or at 12 months could predict the response to intermittent cyclical therapy (ICT) with etidronate, defined in one of two ways: (i) an increase in LS BMD at 24 months (improvement) or (ii) an increase in LS BMD > or = 0.028 g/cm2 (significant improvement). The latter is a precision term calculated from test-retest values for LS BMD in osteoporotic patients. Two hundred and forty-seven patients (32 men; 5 premenopausal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…Indeed, although a significant increase in BMD of trabecular sites was observed in the alendronate‐treated patients, (4) it was shown that no increase in bone mass (i.e., bone volume to total volume [BV/TV] from quantitative histomorphometry on iliac crest bone biopsy specimens) occurred in patients after a 3‐year treatment with alendronate as compared with the placebo group. Significant increases in BMD also were observed in patients under other BPs, (1,5–7) including etidronate (8,2) . These data suggested that parameters other than true bone mass might explain changes in BMD or reduced fracture incidence under treatment.…”
Section: Introductionmentioning
confidence: 72%
“…Indeed, although a significant increase in BMD of trabecular sites was observed in the alendronate‐treated patients, (4) it was shown that no increase in bone mass (i.e., bone volume to total volume [BV/TV] from quantitative histomorphometry on iliac crest bone biopsy specimens) occurred in patients after a 3‐year treatment with alendronate as compared with the placebo group. Significant increases in BMD also were observed in patients under other BPs, (1,5–7) including etidronate (8,2) . These data suggested that parameters other than true bone mass might explain changes in BMD or reduced fracture incidence under treatment.…”
Section: Introductionmentioning
confidence: 72%
“…Существование резистентных к БФ пациентов пред-ставляет потенциальную проблему для клиницистов [4]. Идентифицировать больных с отсутствием ответа или со слабым ответом на БФ можно по характеру динамики уровня биохимических маркеров костного метаболизма через 3 мес от начала лечения [5] или изменения МПК че-рез 6-12 мес [6].…”
Section: Discussionunclassified
“…Известно, что увеличение МПК на фоне лечения БФ происходит медленно, однако в одном из исследований было показано, что любое улучшение МПК через 6 мес яв-ляется предиктором последующего положительного эффе-кта БФ [6]. В нашей пилотной работе для идентификации ответивших и не ответивших на лечение БФ мы выбрали 12-месячный период вмешательства.…”
Section: Discussionunclassified
“…However, a well designed study to predict subsequent BMD response to bisphosphonate from early BMD response suggested that any improvement in BMD at 6 or 12 months is strongly indicative of subsequent BMD response 18. Therefore, we assumed that one year follow-up BMD would be sufficient to classify "non-responder(s)" and "responders".…”
Section: Discussionmentioning
confidence: 99%
“…Although bisphosphonate is known as a potent inhibitor of bone resorption and used for the treatment and prevention of osteoporosis, non-responders to bisphosphonate therapy is of potential concern to clinicians and patients 16. Several studies have been conducted to identify high risk groups of non-responder(s), based on baseline characteristics,14 early changes in biochemical markers of bone turnover17 and early changes in BMD 18. However, little is known about the common characteristics of non-responder(s) to help clinicians decide whether to initiate bisphosphonates or not.…”
Section: Introductionmentioning
confidence: 99%